(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2021)
Background: The availability, accessibility, and effective use of essential medical devices play a vital role in delivering quality health services. Unfortunately, in developing countries, including Kenya, it is estimated that as high as 70 of medical % devices are partially or entirely non-functional. Therefore, this study sought to evaluate the clinical effectiveness, safety, reliability, and acceptability of a locally made low-cost suction aspirator (Maker) by comparing it to the standard of care equipment in a tertiary referral hospital routine setting. Methods: This was an open-label, pragmatic, randomized controlled noninferiority trial. The mixed-methods approach with quantitative and qualitative data collection approaches was used. Women undergoing cesarean section and their babies (where needed) were randomized to either standard of care or Maker equipment for suction during surgery. A noninferiority margin of risk difference between the standard of care and Maker suction equipment was prespecified at 7%. Key informant % interviews were conducted with clinicians and nurses to inform the utility of the Maker equipment. Results: A total of 110 participants were recruited. Of these, 56 and 54 participants were randomly assigned to the standard care and Maker suction equipment arms, respectively. Using a per-protocol approach, suction was reported as successful in 96.4 (54/56) % of the participants in the standard of care arm and 92.6 (50/54) of the participants in the Maker’s arm. % Fifty percent (n=28) of the participants in the standard of care arm, had gauze used in place of the suction machine. Qualitative findings illustrate that the Maker equipment was reliable and acceptable with the improvements made such as overflow protection valve making it the preferred equipment. Conclusion: The Maker equipment is like the standard of care equipment. The high reliability and acceptability, and absence of safety concerns highlights the potential of local development of medical devices to address existing gaps.